Synthesis, characterization and catalytic application of Ru-II-ethylenediamine complex - mesoporous silica as heterogeneous catalyst system in chemo-selective hydrogenation of alpha,beta-unsaturated carbonyl compounds - Ghosh, Anirban; Kumar, R (Microporous and Mesoporous Materials, 2005)
An efficient heterogeneous catalyst system for chemo-selective hydrogenation of alpha,beta-unsaturated aldehydes was synthesized, involving anchoring of a Ru-II-phosphine complex on the inner surfaces of organo-functionalized (propylamine and propylethylenediamine) mesoporous MCM-41 and MCM-48 materials. Powder XRD, SEM and TEM experiments reveal highly ordered hexagonal and cubic patterns of the organically modified MCM-41 and MCM-48 materials, respectively, even after incorporation of Ru complexes. Moreover, the integrity of the Ru complex was retained after anchoring into the mesoporous hosts, which was supported by FTIR, P-31 CP MAS NMR and XPS analyses. This heterogeneous catalyst shows promising activity and chemo-selectivity towards hydrogenation of carbonyl groups in alpha,beta-unsaturated aldehydes. The effects of reaction temperature, reaction time and hydrogen pressure on the activity and selectivity were studied in detail. The anchored solid catalysts can be recycled effectively and reused several times without any loss in activity and selectivity. Although, the initial activity of the same Ru complex when grafted onto the organically modified surfaces of fumed silica is comparable to corresponding MCM41/MCM-48 catalysts, the activity and chemo-selectivity significantly decrease during recycle of the catalyst due to leaching. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: chemo-selective; heterogeneous catalysis; Heterogenization; Hydrogenation; mesoporous materials; organo-functionalization; Ru-II-ethylenediamine complex; unsaturated aldehyde